Características de atributos do solo em ambientes da região Sul do estado do Amazonas - Aquino, Renato Eleoterio de [UNESP] (2014)
Considering the lack of information regarding the different Amazonian environments, the study of soil properties and their behavior in the face of human actions incurred during handling are very important in southern Amazonas. In this sense, the objective of this study is the characterization of soil environments in the southern state of Amazon. In this study soil samples were taken in six different locations of trenches and managements in archaeological black earth soils (ABE) where it has been the characterization and classification. Then were assembled five stitches in southern Amazon them being composed of forest, ABE, agroforestry, cassava and sugar cane. Measurements of CO2, temperature and soil moisture, which were characterized punctually and also performed physical and chemical soil analyzes were made. Mean test, descriptive statistical analyzes, geostatistics and multivariate analyzes were performed on data obtained. It was concluded that hematite and goethite determined by x-ray diffraction and diffuse reflectance spectroscopy in addition to not having significant variations between the soils, shows similar uncontaminated soil anthropogenic Brazilian characteristics. The measured color by diffuse reflectance spectroscopy has been successful to indicate variations between ABE studied, proving to be a novel, effective and promising for indirect quantification of soil properties in a simple and low cost technique. The characterization of physical, chemical and biological attributes in anthropogenic environments in the southern Amazon region, showed that cassava environments and cane sugar are those that come closest to the natural environment Forest. Thus, managements that most contributed to the increased variability of attributes in relation to natural variability of forest and agroforestry were ABE